DFT and DFT+U investigation of some physical properties of CdBr2 by FP-LAPW method and PBE-GGA approximation - Abu Shakhah, Mahmoud; Alarqan, Ayman; Belhadj, Soraya; Sigaa, Khaoula (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : GÉNIE DES PROCÉDÉS, 2023)
In this study, cadmium bromide CdBr2 compound and its distinctive properties were investigated. The focus was on its structural, electronic, and optical propreties. The Wien2k code was employed, based on density functional theory (DFT) using the PBE-GGA approximation. Additionally, the TB-mBJ potential was used to improve the accuracy of the results. A comparison was made between the results obtained before and after applying TB-mBJ, revealing differences in the outcomes. DFT + U (Hubbard correction) was also utilized, but it had minimal impact on the results. Based on the obtained results, it was inferred that the compound is expected to be an insulator with a bandgap of approximately (4.3 eV) and lacks magnetic properties.
OPTION: Chemical Engineering